Targeted gene disruption of the endogenous c-abl locus by homologous recombination with DNA encoding a selectable fusion protein. - Schwartzberg, P L (1990)
We have introduced a substitution mutation into the c-abl locus of murine embryonic stem cells by homologous recombination between exogenously added DNA and the endogenous gene. Model constructs were initially generated that consisted of a promoterless selectable neomycin resistance marker inserted into the v-abl gene of the complete Abelson murine leukemia virus genome, designed to be expressed either as a fusion protein or by translational restart. Tests of these viral genomes for transmission of v-abl and neo markers showed more stable coexpression in a protein fusion construct. The neo fusion was subcloned from this v-abl construct into a promoterless c-abl fragment, and the resulting DNA was used to transform embryonic stem cells. Direct screening of genomic DNAs showed that a high proportion of drug-resistant clones arose from homologous recombination into the endogenous c-abl locus.